HGTree: database of horizontally transferred genes determined by tree reconciliation. Issue Volume 44:Issue D1(2016) (17th November 2015) - Jeong, Hyeonsoo; Sung, Samsun; Kwon, Taehyung; Seo, Minseok; Caetano-Anollés, Kelsey; Choi, Sang Ho; Cho, Seoae; Nasir, Arshan; Kim, Heebal
Abstract: The HGTree database provides putative genome-wide horizontal gene transfer (HGT) information for 2472 completely sequenced prokaryotic genomes. This task is accomplished by reconstructing approximate maximum likelihood phylogenetic trees for each orthologous gene and corresponding 16S rRNA reference species sets and then reconciling the two trees under parsimony framework. The tree reconciliation method is generally considered to be a reliable way to detect HGT events but its practical use has remained limited because the method is computationally intensive and conceptually challenging. In this regard, HGTree (http://hgtree.snu.ac.kr ) represents a useful addition to the biological community and enables quick and easy retrieval of information for HGT-acquired genes to better understand microbial taxonomy and evolution. The database is freely available and can be easily scaled and updated to keep pace with the rapid rise in genomic information.